2018
DOI: 10.5005/jp-journals-10024-2372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Periodontal Indices and Serum Interleukin-27 by One-stage Full-mouth Disinfection and Quadrant Scaling and Root Planing in Periodontitis

Abstract: Considering the benefits of the FMD method, such as patient and dentist comfort, systemic effects, and its cost-effectiveness, use of this method is suggested in patients suffering from periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…225227 Only a few articles have investigated IL-27 in the periodontal region; these studies showed that IL-27 might not be highly expressed in the GCF of chronic periodontitis patients 228 but is upregulated in both GCF and serum after periodontal treatment. 229,230 These clinical data indicated that IL-27 is likely an anti-inflammatory cytokine that participates mainly in the resolution or steady stage of periodontitis.…”
Section: Other Anti-inflammatory Cytokines Involved In Periodontitismentioning
confidence: 99%
“…225227 Only a few articles have investigated IL-27 in the periodontal region; these studies showed that IL-27 might not be highly expressed in the GCF of chronic periodontitis patients 228 but is upregulated in both GCF and serum after periodontal treatment. 229,230 These clinical data indicated that IL-27 is likely an anti-inflammatory cytokine that participates mainly in the resolution or steady stage of periodontitis.…”
Section: Other Anti-inflammatory Cytokines Involved In Periodontitismentioning
confidence: 99%
“…A later report indicated that this full-mouth treatment approach resulted in superior clinical outcomes and microbiological e ects than conventional quadrant SRP (control), regardless of the adjunctive use of chlorhexidine . However, morerecent studies from other research centres have not been able to demonstrate an advantage of full-mouth scaling (FMS) within 24 hours over the control regimen (Afacan 2020;Apatzidou 2004;Babaloo 2018;Del Peloso 2008;Fonseca 2015;Graziani 2015;Jervøe-Storm 2006;Koshy 2005;Loggner Gra 2009;Pontillo 2018;Predin 2014;Roman-Torres 2018;Santuchi 2015;Soares 2015;Swierkot 2009;Wennström 2005;Zanatta 2006;Zijnge 2010).…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…19 Specifically, in patients with periodontitis, it has been reported that, among others, periodontal treatment performed through a full-mouth scaling and root planing (FM-SRP) approach was demonstrated to be efficacious in reducing several clinical outcomes and serum markers of systemic inflammatory risk. [20][21][22][23] There is growing interest in evaluating the impact of periodontal treatment on early biomarkers related to early CVD risk and evaluating the effects of biomarker levels on the long-term efficacy of periodontal therapy. For the above-mentioned reasons, the aim of the present study was to assess the impact of two non-surgical periodontal treatment protocols on serum NT-proBNP and related CVD biomarkers in patients with periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Another preliminary evidence reported that, in comparison with healthy subjects, periodontal inflammation could increase CVD risk through the main role exerted by the upregulation of inflammatory mediators such as hs‐CRP and NT‐proBNP 15 and that periodontal treatment could determine positive effects on systemic inflammatory CVD markers such as hs‐CRP, 16 ECM‐1, 17 or neutrophil gelatinase‐associated lipocalin (NGAL), 18 even through with variability in the reported outcomes among trials 19 . Specifically, in patients with periodontitis, it has been reported that, among others, periodontal treatment performed through a full‐mouth scaling and root planing (FM‐SRP) approach was demonstrated to be efficacious in reducing several clinical outcomes and serum markers of systemic inflammatory risk 20–23 …”
Section: Introductionmentioning
confidence: 99%